1978
DOI: 10.1111/j.1365-2044.1978.tb08347.x
|View full text |Cite
|
Sign up to set email alerts
|

Forum Cardio‐respiratory effects of nitrous oxide:oxygen:halothane anaesthesia administered to dental outpatients in the upright position

Abstract: There has been much discussion concerning the relative merits of general anaesthesia in the upright and horizontal postures for dental patients.Bourne' has drawn attention to the vulnerability of the brain should hypotension occur during such a procedure with the patient seated upright. He has suggested that 'fainting' may occur and pass unnoticed during induction of anaesthesia. There is considerable material available in the literature on the cardio-respiratory responses under such circumstances,'-" but rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1981
1981
2002
2002

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Hypoxaemia during dental extraction under nasal mask anaesthesia is often rapid in onset, not always obvious clinically [1,[13][14][15], and reported to be a major contributory factor to death from dental anaesthesia [16]. Pulse oximetry provides an advance in monitoring by detecting small reductions in oxygen saturation and displaying trends [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxaemia during dental extraction under nasal mask anaesthesia is often rapid in onset, not always obvious clinically [1,[13][14][15], and reported to be a major contributory factor to death from dental anaesthesia [16]. Pulse oximetry provides an advance in monitoring by detecting small reductions in oxygen saturation and displaying trends [10,17].…”
Section: Discussionmentioning
confidence: 99%
“…It is not at all easy to keep a strong, unpremedicated man anaesthetized with enflurane when using the commonly available vaporizers which give only 5% enflurane. Patients are reported to wake more quickly and more clear-headed with enflurane, and there is a lower incidence of arrythmias, which are extremely common during halothane anaesthesia, especially during ENT and dental procedures (AI Khishali et al 1978).…”
Section: Maintenancementioning
confidence: 99%
“…In spite of this Bourne gained supporters and the issue continued to divide dental anaesthetists, even though there is ample research evidence to demons-trate that arterial blood pressure does not show any significant fall. Several studies compared arterial blood pressure in patients undergoing dental anaesthesia in different positions, including sitting and fully supine, and concluded that there was no evidence to support the use of the supine position for outpatient dental anaesthesia [8,9]. Coplans and Curson also concluded that there was no consistent relationship between mortality and position, while identifying more respiratory problems in patients who were supine [5].…”
mentioning
confidence: 99%